A entonação e o sujeito: uma análise discurso-enunciativa sob a perspectiva da linguagem de Volóchinov e Bakhtin - Santos, Jaciara Fernandes dos (2022)
In this text, we observe the construction of the meaning of the utterance through the intonation concept of the Bakhtinian circle and everyday speech. We seek to relate Voloshinov and Bakhtin's theory of language perspective (2018, 2019) regarding the concepts of social horizon, situation and intonation with the statement in the form of a statement. The purpose of this proposal is to analyze the effects of meaning arising from intonation in a statement by a subject participating in a social program in the north of RS.